Expression in popular music singing as embodied and interpersonal - Juntunen, Marja-Leena; Arlin, Elina P.; Liira, Katri (Frontiers in Education, 2023)
This article presents theorical viewpoints for considering and understanding expression in popular music singing and pedagogy from the perspective of embodiment as outlined in Merleau-Ponty’s phenomenological philosophy. In our examination, we apply his interpretations of such notions as intentionality, body schema, gesture, reversibility and intersubjectivity to bring forth and discuss the holistic, embodied, and interpersonal nature of voice expression in singing. We argue that expression should be viewed as an intentional activity, based on the body’s innate mindful functioning as a whole, and in singing guided by the lyrics and emotions to be communicated. We propose that this requires a "free voice" singing technique, based on healthy vocal production, that also allows for immediacy of expression as and through gestures that bring the meaning into existence. We further argue that expression is an interpersonal, interactive, and intersubjective process in which the performer and listener influence each other in many ways. The reversibility of perception in expression means that perception and the object perceived are intertwined and action and perception are interconnected. There is also a gap in reversibility, which implies that perception of (one's own) expression is never complete. In addition to our theoretical arguments, we make pedagogical suggestions, such as that the body itself has a lot of understanding of how and should be trusted in singing, both in terms of voice production and expression. Expression should not be primarily approached as a technical issue but taught in connection with and through expression. Expression should be viewed as from inside out, not the opposite. This means that expression builds on one’s personality and (emotional) experiences.